A RARE DIAGNOSIS IN 3RD TRIMESTER PREGNANCY OF FUNCTIONING LEFT PHAEOCHROMOCYTOMA AND PARAGANGLIOMA: A CASE REPORT - Vergis, Melissa; Yong, Sy Liang; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Phaeochromocytoma or paraganglioma in pregnancy is extremely rare, with a frequency of 0.007% of all pregnancies. If unrecognized, it has high maternal and fetal mortality risk. RESULTS A 34-year-old G2P1 female at 34 weeks gestation with GDM on insulin was referred for further workup. She had previously been detected to have a left suprarenal mass (8.5 x 5.2 x 5.8 cm) by ultrasound during her first pregnancy, and underwent caesarean section (CS) at 36 weeks for severe pre-eclampsia with impending eclampsia. Postpartum, her anti-hypertensives were discontinued within 2 weeks. She subsequently defaulted further follow-up. She had paroxysmal symptoms of headache and palpitation once to twice a week during the current pregnancy. Blood pressure in the ward was <140/90. KUB ultrasound showed a heterogeneous mass with cystic component arising from the left suprarenal region (9.6cm x 7.7cm x9.6cm), with another smaller mass (6.0cm x 5.6cm) lateral to this. 24- hour urine catecholamines revealed elevated epinephrine 7.55 times above the upper limit of normal (ULN) at 151.0 mcg/day (Normal: 0.5 –20.0) while norepinephrine and dopamine were raised 1.98 and 1.91 times above ULN respectively. The patient was then referred to an endocrine tertiary centre for expert multidisciplinary care. She was started on prazosin and underwent elective CS 1 week later at 36 weeks gestation, delivering a 2.7kg baby. An adrenal CT scan 3 weeks postpartum showed left suprarenal masses of mixed density and heterogeneous enhancement (9.4cm x 9.2cm x 8.3cm and 5.7cm x 6.4cm x 6.6cm). Her alpha-blocker was changed to Phenoxybenzamine 2 weeks prior to surgery. She underwent open adrenalectomy 3 months postpartum with excision of left paraganglioma (7 x 7 cm) and left phaeochromocytoma (10 x 10 cm) together with the normal-looking left adrenal gland. CONCLUSION In phaeochromocytoma and paraganglioma (PPGL) in pregnancy, multidisciplinary coordination is essential for effective management in terms of appropriate mode of delivery, timing of surgery, anaesthesia as well as adequate pre-operative medical preparation.